INCREASING READING COMPREHENSION AND SUMMARY WRITING ACHIEVEMENTS BY USING RAP STRATEGY WITH 100 FAMOUS STORIES APPLICATION - Mitra Afriadeni; Eryansyah Eryansyah; Rita Inderawati (English Review: Journal of English Education, 2021)
This study aimed to investigate the students’ writing achievement between before and after the students were taught by using RAP strategy with 100 Famous Stories application. It involved 68 students as pasrticipants and used quasi experimental research method. The result of this study were analyzed by using paired sample t-test and independent sample t-test with the SPPS Version 22.The result of the study for the experimental group showed that the significance level of p was <0.05. The critical value of t-table was lower than t-obtained (22.333>2.036) for reading and (9.162>2.036) for writing. In other words, there was a significance difference in reading comprehension and writing achievement before and after the treatments in experimental group. Furthermore, the result of the independent t-test showed that the critical value of t-table was lower than t-obtained (5.936>1.997) for reading and (7.852>1.997) for summary writing, that is to say there was a significance difference in reading comprehension and writing summary acheievement of the eleventh grade students of SMA Srijaya Negara who were taught by using RAP Strategy with 100 Famous Stories Application and those who were not. It concludes that RAP strategy with 100 famous stories application could improve the students’ reading comprehension and writing achievements.